Bridging competitive advantage and trade-off theory: Financial management practices among coconut MSMEs in North Minahasa - Aldrian Victor Pangemanan; Herman Karamoy; Robert Lambey (Yayasan Widyantara Nawasena Raharja, 2026)
Coconut-based Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting North Minahasa's regional economy through value-added production and employment generation. However, financial management among these enterprises remains weak, often marked by informal practices, poor record-keeping, and the absence of financial reporting. This study analyzes the implementation of financial management from the aspects of planning, organizing, actuating, controlling, and reporting (POACR) among coconut-based MSMEs in North Minahasa Regency. Using a qualitative descriptive case study approach, data were obtained through in-depth interviews with five purposively selected informants representing three coconut product sub-sectors (coconut fiber handicraft, copra, and coconut shell charcoal processing) in Likupang Timur and Airmadidi Sub-districts, together with field observations and document analysis over a defined fieldwork period. The study applied Competitive Advantage Theory (Porter, 2008) and Trade-Off Theory (Myers, 1984) as interpretive, sensitizing frameworks to assess how financial management shapes MSME competitiveness and financing strategies. Results show that financial management remains largely informal, relying on owners' intuition rather than formal documentation. Planning is done mentally, organizing and actuating remain undifferentiated from the owner's daily role, controlling relies on direct supervision, and reporting is the weakest and most inconsistent element across all three sub-sectors. Despite these weaknesses, MSMEs demonstrate adaptive resilience, cautious financing behavior consistent with Trade-Off Theory, and strong local resource utilization consistent with Competitive Advantage Theory. The study recommends strengthening financial literacy, promoting digital record-keeping, and encouraging government and institutional support to improve financial structure and competitiveness.